Noise Control Transmission Methods of the Combustion Engine by Means of Reduction of the Vibration - Stanislav ŽIARAN; Ondrej CHLEBO (Archives of Acoustics, 2016)
Transmission of vibroacoustic energy from an internal combustion engine (ICE) to its surroundings largely depends on how it is mounted, on available transmission paths and on the construction of the vehicle body and/or its surrounding structures. This is especially true in low speed engines in enclosed areas which generate perceptually weak noise, but strong low-frequency waves which energy has a negative impact on human health, comfort and driving safety especially in prolonged exposure to the source. The primary aim of the article was to analyse components of the ICE unit which had a determining impact on the reduction of low-frequency waves. Thus, the structurally transmitted noise from the ICE to its surrounding structure (body of the passenger vehicle) was analysed. The results of the vibroacoustic measurements were compared to modal analysis in order to determine possible resonance sources in the vehicle body and/or for assessing the influence of the vehicles safety gear on the generated vibroacoustic energy transfer into the cabin area of the passenger vehicle. Measurements were made for a passenger vehicle at rest and operating in its most common operational speed as well as for the stationary ICE of a cogenerate unit (CGU). Measurements and FFT analysis were used for the detection of the vibroacoustic energy sound pressure level (noise) and mechanical vibration. Firstly, the low-frequency noise sources were determined and their direct effects on the human body were investigated. Finally, this paper suggests some measures which may contribute to the reduction of undesirable vibroacoustic energy in enclosed areas.